Effect of high temperature annealing (T > 1650 °C) on the morphological and electrical properties of p-type implanted 4H-SiC layers. (April 2019) - Spera, M.; Corso, D.; Di Franco, S.; Greco, G.; Severino, A.; Fiorenza, P.; Giannazzo, F.; Roccaforte, F.
Abstract: This work reports on the effect of high temperature annealing on the electrical properties of p-type implanted 4H-SiC. Ion implantations of Aluminum (Al) at different energies (30–200 keV) were carried out to achieve 300 nm thick acceptor box profiles with a concentration of about 10 20 at/cm 3 . The implanted samples were annealed at high temperatures (1675–1825 °C). Morphological analyses of the annealed samples revealed only a slight increase of the surface roughness RMS up to 1775 °C, while this increase becomes more significant at 1825 °C (RMS = 1.2 nm). Room temperature Hall measurements resulted in a hole concentration in the range 0.65–1.34 × 10 18 /cm 3 and mobility values in the order of 21–27 cm 2 V −1 s −1 . The temperature dependent electrical measurements allowed to estimate an activation energy of the Al-implanted specie of about 110 meV (for the post-implantation annealing at 1675 °C) and a fraction of active p-type Al-dopant ranging between 39% and 56%. The results give useful indications for the fabrication of 4H-SiC JBS and MOSFETs.